Dialectic tensions and role negotiation: experiences of post-deployment among married military mothers - Pratt, Samantha M. (Kansas State University, 2018)
Married military mothers are placed in a unique position where they have to navigate many tensions, including tensions between masculinity and femininity as well as tensions between the public sphere (work) and the private sphere (home). When military mothers who are married deploy and are physically separated from the home, shifts in household and family roles occur. Upon return from deployment, married military mothers have to communicate with their spouses to reestablish and renegotiate their domestic and childcare roles. Therefore, considering distinctive challenges and experiences faced by married military women with children, this qualitative analysis provides an in-depth look at married military mothers’ subjective experiences using the concept of role dialectics. The analysis of 11 in-depth interviews with married military mothers indicates that roles and responsibilities are negotiated communicatively, drawing on expectations in various interactions. Expectations are communicated nonverbally by relying on gendered roles, past experiences, and nonverbal cues. Verbally expectations are communicated to reassume, coordinate, learn, divide and resolve roles and responsibilities. Regardless of the verbal or nonverbal communication strategies, all military mothers actively resumed traditionally gendered roles and responsibilities post-deployment when negotiating gender role tensions. This study enhances understanding of communication patterns used by married military mothers to negotiate roles and responsibilities throughout the deployment cycle. Moreover, the researcher offers guidance on effective communication practices to help married military mothers navigate tensions and provide families with constructive strategies for post-deployment. Results also contribute to a larger body of work/life literature on mothers in the military, especially pertaining to deployments, while advancing the concept of role dialectics.
Keywords: ReintegrationMarried military mothers; Role dialectics